Evaluation of Two Alternative Procedures for Measuring Airflow Resistance of Sound Absorbing Materials - REY, Romina del; ALBA, Jesus; ARENAS, Jorge P.; RAMIS, Jaime (Archives of Acoustics, 2013)
It is well known that sound absorption and sound transmission properties of open porous materialsare highly dependent on their airflow resistance values. Low values of airflow resistance indicate littleresistance for air streaming through the porous material and high values are a sign that most of the poresinside the material are closed. The laboratory procedures for measuring airflow resistance have been stan-dardized by several organizations, including ISO and ASTM for both alternate flow and continuous flow.However, practical implementation of these standardized methods could be both complex and expensive.In this work, two indirect alternative measurement procedures were compared against the alternate flowstandardized technique. The techniques were tested using three families of eco-friendly sound absorbentmaterials: recycled polyurethane foams, coconut natural fibres, and recycled polyester fibres. It is foundthat the values of airflow resistance measured using both alternative methods are very similar. There isalso a good correlation between the values obtained through alternative and standardized methods.